2022
DOI: 10.1136/bjophthalmol-2021-320084
|View full text |Cite
|
Sign up to set email alerts
|

NDP-related retinopathies: clinical phenotype of female carriers

Abstract: Background/aimsNorrin cysteine knot growth factor (NDP) located on the X chromosome, was previously reported to cause Norrie disease and familial exudative vitreoretinopathy (FEVR), which are blindness-causing ocular disorders, in males. In this study, we aimed to explore the clinical characteristics of female carriers with NDP mutations.MethodsTwelve female carriers from 11 unrelated families with pathogenic NDP mutations were recruited. Clinical data were collected from the NDP carriers. Comprehensive ocular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Most patients with FEVR caused by the NDP gene are male, some female patients were reported. The research of Huang et al (22) revealed that 33.3% (8/24) female carriers had typical familial exudative vitreoretinopathy phenotype, 33.3% (8/24) had mild vascular abnormalities. The reason of such broad spectrum of phenotypes observed in NDP variant female carriers presumed to X-chromosome inactivation (XCI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients with FEVR caused by the NDP gene are male, some female patients were reported. The research of Huang et al (22) revealed that 33.3% (8/24) female carriers had typical familial exudative vitreoretinopathy phenotype, 33.3% (8/24) had mild vascular abnormalities. The reason of such broad spectrum of phenotypes observed in NDP variant female carriers presumed to X-chromosome inactivation (XCI).…”
Section: Discussionmentioning
confidence: 99%
“…It was consisted with the predictions of spliceAI and RDDC software. Several variants in the start code (c.1A > G, c.2T > G, c.2T > C and c.2T > A) were reported as "disease-causing mutations (DM)" of Norrie disease (20)(21)(22). The research of Li (23) et al indicated that NDP gene c.174 + 1G > A in a Chinese family with Norrie disease lead to deletion of 246 bp at the 3′ end of exon 2. c.174 + 1G > A and c.-167_174delinsAAGG have the same impact on the coding region.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in our previous study, female carriers of NDP mutations were found to have retinal vascular abnormalities, and nearly one-third of eyes presented with a typic familial exudative vitreoretinopathy presence in fundus fluorescein angiography. 30 Females with CACNA1F mutations have rarely been reported, although mild-to-moderate loss of vision or electrophysiologic changes have been mentioned in sporadic cases. 31 The female carrier phenotype has not been documented in association with the NYX and OPN1MW mutations 7 ; however, the potential mechanism of X-chromosome inactivation has been suggested.…”
Section: Discussionmentioning
confidence: 99%